2020
DOI: 10.1101/2020.01.10.901470
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Serological evidence of Rift Valley fever infection and risk factors among one-humped camels (Camelus dromedarius) in Northern Nigeria

Abstract: 43 Background: Rift Valley fever (RVF) is a zoonotic disease that has become emerging and re-44 emerging in some regions of the world, infecting livestock and humans. One-humped camels are 45 important economic livestock species in Africa used for traction, transportation, and food.46 Regional and international trade has continued to increase the risk of this disease, spreading 47 widely and causing severe economic and public health catastrophes in affected regions. In spite 48 of these risks, there is a deart… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 35 publications
(38 reference statements)
1
1
0
Order By: Relevance
“…The overall seroprevalence of 20.7% reported in this study was observed to be almost similar to the 19.9% reported in a recent study from the two northwestern states of Jigawa and Katsina in Nigeria (Musa et al, 2020). This may be because the two states share similar characteristics with Borno State since all the three states share international borders with other countries closer to the hotspots of the disease.…”
Section: Discussionsupporting
confidence: 88%
“…The overall seroprevalence of 20.7% reported in this study was observed to be almost similar to the 19.9% reported in a recent study from the two northwestern states of Jigawa and Katsina in Nigeria (Musa et al, 2020). This may be because the two states share similar characteristics with Borno State since all the three states share international borders with other countries closer to the hotspots of the disease.…”
Section: Discussionsupporting
confidence: 88%
“…It is likely that the first report of RVFV was in 1959 in Nigeria [ 126 ]. However, the latest RVFV case was detected in 2016 in Mali, Niger, and Nigeria [ 122 , 125 , 127 ], and this is the first occurrence of RVFV in Niger. RVFV was detected in culicine mosquitoes and serological investigations in humans, bats, livestock, horses, and camels.…”
Section: Discovery Of Mosquito-associated Virusesmentioning
confidence: 99%